Heterogeneity of astrocytes: from development to injury - single cell gene expression - Rusnakova, Vendula; Honsa, Pavel; Dzamba, David; Ståhlberg, Anders; Kubista, Mikael; Anderova, Miroslava (PloS one, 2013)
Astrocytes perform control and regulatory functions in the central nervous system; heterogeneity among them is still a matter of debate due to limited knowledge of their gene expression profiles and functional diversity. To unravel astrocyte heterogeneity during postnatal development and after focal cerebral ischemia, we employed single-cell gene expression profiling in acutely isolated cortical GFAP/EGFP-positive cells. Using a microfluidic qPCR platform, we profiled 47 genes encoding glial markers and ion channels/transporters/receptors participating in maintaining K(+) and glutamate homeostasis per cell. Self-organizing maps and principal component analyses revealed three subpopulations within 10-50 days of postnatal development (P10-P50). The first subpopulation, mainly immature glia from P10, was characterized by high transcriptional activity of all studied genes, including polydendrocytic markers. The second subpopulation (mostly from P20) was characterized by low gene transcript levels, while the third subpopulation encompassed mature astrocytes (mainly from P30, P50). Within 14 days after ischemia (D3, D7, D14), additional astrocytic subpopulations were identified: resting glia (mostly from P50 and D3), transcriptionally active early reactive glia (mainly from D7) and permanent reactive glia (solely from D14). Following focal cerebral ischemia, reactive astrocytes underwent pronounced changes in the expression of aquaporins, nonspecific cationic and potassium channels, glutamate receptors and reactive astrocyte markers.
Keywords: polymerázová řetězová reakce; antigeny; Astrocytes; mozková kůra; imunohistochemie; S-100 kalcium vázající protein G, podjednotka beta; S100 Calcium Binding Protein beta Subunit; Flow Cytometry; Antigens; proteoglykany; zelené fluorescenční proteiny; průtoková cytometrie; Animals; Proteoglycans; myši transgenní; Immunohistochemistry; gliový fibrilární kyselý protein; zvířata; Glial Fibrillary Acidic Protein; Green Fluorescent Proteins; myši; neuroglie; Polymerase Chain Reaction; Neuroglia; astrocyty; Mice; Mice, Transgenic; Cerebral Cortex